An Unusual Case of Multiple Myeloma with Light-Chain Cast Nephropathy Secondary to a Very Large Plasmacytoma without Bone Marrow Involvement - Justin Komisarof; Jodi Lipof; Joseph DiTursi; Amit Chowdhry; Hae Yoon Grace Choung; W. Richard Burack; Louis Constine; Frank Passero (Case Reports in Hematology)
Here, we report a case of a patient who presented to Strong Memorial Hospital with new-onset renal failure and anemia and was found to have multiple myeloma with lambda light-chain cast nephropathy secondary to a very large (14 cm × 14 cm × 12 cm) plasmacytoma without bone marrow involvement. This case is notable as solitary plasmacytomas are almost never seen with concomitant myeloma-defining CRAB criteria or significantly elevated serum free light-chain ratios. Although solitary plasmacytomas are typically definitively treated with radiation, this case highlights that systemic treatment may be helpful in certain clinical scenarios.